Critical roles of intestinal epithelial vitamin D receptor signaling in controlling gut mucosal inflammation. Issue 148 (April 2015) - Li, Yan Chun; Chen, Yunzi; Du, Jie
Highlights: Intestinal epithelial VDR inhibits colitis by protecting the mucosal barrier. Intestinal epithelial VDR levels are reduced in patients with IBD. Intestinal epithelial VDR is down-regulated by a microRNA-mediated mechanism. VDR is a key molecule in a regulatory circuit controlling mucosal inflammation. Increasing gut epithelial VDR levels are a valuable strategy for IBD treatment. Abstract: Although vitamin D receptor (VDR) is highly expressed in the intestine, the role of VDR signaling in the gut is not fully understood. Our recent studies unveil a regulatory circuit that centers gut epithelial VDR as a key molecule in the control of mucosal inflammation and colitis development. On the one hand, intestinal epithelial VDR signaling protects the integrity of the mucosal barrier by inhibiting inflammation-induced epithelial cell apoptosis. This barrier-protecting, anti-colitic activity is independent of the non-epithelial immune VDR actions. A healthy and intact mucosal barrier prevents bacterial invasion and thus reduces mucosal inflammation. On the other hand, inflammation in turn down-regulates epithelial VDR expression by inducing VDR-targeting microRNA-346, thus compromising mucosal barrier functions. Consistently, colonic epithelial VDR levels are markedly reduced in patients with inflammatory bowel diseases or in experimental colitis models, whereas vitamin D analog therapy that ameliorates colitis up-regulates epithelial VDR. Thus, gut epithelial VDR signaling appears to play an essential role in controlling mucosal inflammation and thus could be a useful therapeutic target in the management of inflammatory bowel diseases. This article is part of a special issue entitled '17th Vitamin D Workshop' .